Theory Abs_Int1_parity_ITP

theory Abs_Int1_parity_ITP
imports Abs_Int1_ITP
(* Author: Tobias Nipkow *)

theory Abs_Int1_parity_ITP
imports Abs_Int1_ITP
begin

subsection "Parity Analysis"

datatype parity = Even | Odd | Either

text{* Instantiation of class @{class preord} with type @{typ parity}: *}

instantiation parity :: preord
begin

text{* First the definition of the interface function @{text"\<sqsubseteq>"}. Note that
the header of the definition must refer to the ascii name @{const le} of the
constants as @{text le_parity} and the definition is named @{text
le_parity_def}. Inside the definition the symbolic names can be used. *}


definition le_parity where
"x \<sqsubseteq> y = (y = Either ∨ x=y)"

text{* Now the instance proof, i.e.\ the proof that the definition fulfills
the axioms (assumptions) of the class. The initial proof-step generates the
necessary proof obligations. *}


instance
proof
fix x::parity show "x \<sqsubseteq> x" by(auto simp: le_parity_def)
next
fix x y z :: parity assume "x \<sqsubseteq> y" "y \<sqsubseteq> z" thus "x \<sqsubseteq> z"
by(auto simp: le_parity_def)
qed

end

text{* Instantiation of class @{class SL_top} with type @{typ parity}: *}

instantiation parity :: SL_top
begin


definition join_parity where
"x \<squnion> y = (if x \<sqsubseteq> y then y else if y \<sqsubseteq> x then x else Either)"

definition Top_parity where
"\<top> = Either"

text{* Now the instance proof. This time we take a lazy shortcut: we do not
write out the proof obligations but use the @{text goali} primitive to refer
to the assumptions of subgoal i and @{text "case?"} to refer to the
conclusion of subgoal i. The class axioms are presented in the same order as
in the class definition. *}


instance
proof
case goal1 (*join1*) show ?case by(auto simp: le_parity_def join_parity_def)
next
case goal2 (*join2*) show ?case by(auto simp: le_parity_def join_parity_def)
next
case goal3 (*join least*) thus ?case by(auto simp: le_parity_def join_parity_def)
next
case goal4 (*Top*) show ?case by(auto simp: le_parity_def Top_parity_def)
qed

end


text{* Now we define the functions used for instantiating the abstract
interpretation locales. Note that the Isabelle terminology is
\emph{interpretation}, not \emph{instantiation} of locales, but we use
instantiation to avoid confusion with abstract interpretation. *}


fun γ_parity :: "parity => val set" where
"γ_parity Even = {i. i mod 2 = 0}" |
"γ_parity Odd = {i. i mod 2 = 1}" |
"γ_parity Either = UNIV"

fun num_parity :: "val => parity" where
"num_parity i = (if i mod 2 = 0 then Even else Odd)"

fun plus_parity :: "parity => parity => parity" where
"plus_parity Even Even = Even" |
"plus_parity Odd Odd = Even" |
"plus_parity Even Odd = Odd" |
"plus_parity Odd Even = Odd" |
"plus_parity Either y = Either" |
"plus_parity x Either = Either"

text{* First we instantiate the abstract value interface and prove that the
functions on type @{typ parity} have all the necessary properties: *}


interpretation Val_abs
where γ = γ_parity and num' = num_parity and plus' = plus_parity
proof txt{* of the locale axioms *}
fix a b :: parity
assume "a \<sqsubseteq> b" thus "γ_parity a ⊆ γ_parity b"
by(auto simp: le_parity_def)
next txt{* The rest in the lazy, implicit way *}
case goal2 show ?case by(auto simp: Top_parity_def)
next
case goal3 show ?case by auto
next
txt{* Warning: this subproof refers to the names @{text a1} and @{text a2}
from the statement of the axiom. *}

case goal4 thus ?case
proof(cases a1 a2 rule: parity.exhaust[case_product parity.exhaust])
qed (auto simp add:mod_add_eq)
qed

text{* Instantiating the abstract interpretation locale requires no more
proofs (they happened in the instatiation above) but delivers the
instantiated abstract interpreter which we call AI: *}


interpretation Abs_Int
where γ = γ_parity and num' = num_parity and plus' = plus_parity
defines aval_parity is aval' and step_parity is step' and AI_parity is AI
..


subsubsection "Tests"

definition "test1_parity =
''x'' ::= N 1;;
WHILE Less (V ''x'') (N 100) DO ''x'' ::= Plus (V ''x'') (N 2)"


value "show_acom_opt (AI_parity test1_parity)"

definition "test2_parity =
''x'' ::= N 1;;
WHILE Less (V ''x'') (N 100) DO ''x'' ::= Plus (V ''x'') (N 3)"


value "show_acom ((step_parity \<top> ^^1) (anno None test2_parity))"
value "show_acom ((step_parity \<top> ^^2) (anno None test2_parity))"
value "show_acom ((step_parity \<top> ^^3) (anno None test2_parity))"
value "show_acom ((step_parity \<top> ^^4) (anno None test2_parity))"
value "show_acom ((step_parity \<top> ^^5) (anno None test2_parity))"
value "show_acom_opt (AI_parity test2_parity)"


subsubsection "Termination"

interpretation Abs_Int_mono
where γ = γ_parity and num' = num_parity and plus' = plus_parity
proof
case goal1 thus ?case
proof(cases a1 a2 b1 b2
rule: parity.exhaust[case_product parity.exhaust[case_product parity.exhaust[case_product parity.exhaust]]]) (* FIXME - UGLY! *)
qed (auto simp add:le_parity_def)
qed


definition m_parity :: "parity => nat" where
"m_parity x = (if x=Either then 0 else 1)"

lemma measure_parity:
"(strict{(x::parity,y). x \<sqsubseteq> y})^-1 ⊆ measure m_parity"
by(auto simp add: m_parity_def le_parity_def)

lemma measure_parity_eq:
"∀x y::parity. x \<sqsubseteq> y ∧ y \<sqsubseteq> x --> m_parity x = m_parity y"
by(auto simp add: m_parity_def le_parity_def)

lemma AI_parity_Some: "∃c'. AI_parity c = Some c'"
by(rule AI_Some_measure[OF measure_parity measure_parity_eq])

end